An Institution to «Give a Child a Family»? The Outdated Framework of Italian Adoption Law - Cesarano, Fabrizia (CUADERNOS DE DERECHO TRANSNACIONAL, 2026)
The paper examines the Italian legal framework on adoption, highlighting both its structural and subjective limitations, which undermine its full adherence to the principle of the best interests of the child. Despite the solidaristic rationale underlying Law No. 184 of 1983, the rigid dichotomy between foster care and adoption fails to reflect the complexity of  contemporary family dynamics, particularly in situations of semi-abandonment, where emotional ties with the biological family persist despite parental inadequacy. Moreover, full adoption remains conditional upon marriage, excluding unmarried couples, same-sex unions and single persons, in tension with constitutional and conventional principles of equality and family pluralism. In the absence of comprehensive legislative reform, courts have sought to address these gaps through flexible interpretations, especially via special adoption, yet such judicial solutions lack the legal certainty that only systematic legislative intervention—also in light of comparative European experiences—can provide.
Keywords: adoption; best interests of the child; family law; civil unions; social parenthood